Early hydration properties of Portland cement with lab-synthetic calcined stöber nano-SiO2 particles as modifier. (September 2022) - Sun, Jinfeng; Shi, Zhiqiang; Dai, Jinyu; Song, Xinyu; Hou, Guihua
Abstract: Nano-SiO2 is a brilliant candidate that endows cement-based materials excellent properties. However, its agglomeration in cement matrix is still an urgent problem. In order to address this issue, well-dispersed calcined stöber nano-SiO2 (CSNS) was prepared as modifier for Portland cement in this work. Monodisperse stöber nano-SiO2 (SNS) was firstly synthesized by using the traditional stöber method and then it was calcined to form CSNS. A series of properties including morphology and structure information of SNS and CSNS were obtained by using scanning electron microscope (SEM), particle size analyzer, X-ray diffraction (XRD), and fourier transform infrared spectroscopy (FT-IR). Their potential pozzolanic activity was also evaluated by using a simulated pore solution method and the possible reaction products were analyzed by using SEM and thermogravimetric (TG) analysis. Finally, their effects on early hydration properties of Portland cement were preliminarily investigated by using isothermal calorimetry, XRD, TG and compressive strength tests. The experimental results showed that both SNS and CSNS with high dispersity and uniform size within 100 nm were successfully prepared. However, both of them present low pozzolanic activity within 3 days. When 2 wt% SNS was added to cement, the occurrence of acceleration period was slightly delayed and the corresponding maximum heat flow was significantly reduced. Its addition also decreased both hydration degree of the cement paste and the compressive strength of the mortar at 1 day and 3 days. On the contrary, CSNS effectively overcame these negative effects of SNS on cement hydration, and further accelerated cement hydration. Compared with the Portland cement, the addition of 2 wt% CSNS significantly increased the cumulative heat released with 72 h, and cement hydration degree and compressive strength at each curing age. This is because the hydroxyl (-OH) group was removed after calcination of SNS, which made the well-dispersed CSNS better accelerate cement hydration by effective nucleation sites and filler effects. The findings of this work can provide a guidance for the application of well-dispersed nano-materials prepared based on stöber method to effectively modify the performance of cement-based materials.